Analisis Hak Asasi Manusia Dan Konstitusionalitas Putusan Mahkamah Konstitusi - Eva Naura Maharani; Akmal Haris; Nazwa Hawwa Audica; Febriyana Nur Aziza Sagita Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
This research uses three (three) different approach models, namely statutory approach, case method, and conceptual approach. The constitution contains a number of concepts and standards, as well as provisions that defend and uphold human rights, according to das soll. However, the rules outlined in das sollen do not correspond to reality. Surprisingly, the authorities often ignore backwardness, poverty, and even oppression. Two main objectives that are interesting to be researched by the author in this regard are: to find out the interpretation of the Constitutional Court at stipulation column 28J clause (2) 1945 Composition concerning limitation about human rights and under what circumstances limitation about human rights may be declared unconstitutional by a Constitutional Court.